2007
DOI: 10.1007/s11172-007-0199-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-solvated aluminum hydride. Crystallization from diethyl ether-benzene solutions

Abstract: Crystallization of non solvated aluminum hydride from a diethyl ether-benzene mixed solvent was studied. The desolvation of AlH 3 •(Et 2 O) x etherate in solution and the crystalliza tion of α AlH 3 during polythermal heating of the solution occur only in the presence of ≥10 wt.% LiAlH 4 . The process is multistage, and the crystallization begins with the formation of the AlH 3 •0.25Et 2 O solvate, which recrystallizes in the solid phase into γ AlH 3 and then α AlH 3 . Four crystalline modifications of aluminu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Previous work of Brower et al indicated that the etherated AlH 3 forms translucent spheres after precipitating from solution. According to Bulychev et al [18] the etherated material has a chemical composition close to AlH 3 ·0.25Et 2 O and although it is generally amorphous, it may form a crystalline phase with an orthorhombic structure and unit cell parameters a = 9.90Å; b = 8.54Å, c = 12.05 (±0.01)Å.…”
Section: Synthesis and Morphologymentioning
confidence: 99%
“…Previous work of Brower et al indicated that the etherated AlH 3 forms translucent spheres after precipitating from solution. According to Bulychev et al [18] the etherated material has a chemical composition close to AlH 3 ·0.25Et 2 O and although it is generally amorphous, it may form a crystalline phase with an orthorhombic structure and unit cell parameters a = 9.90Å; b = 8.54Å, c = 12.05 (±0.01)Å.…”
Section: Synthesis and Morphologymentioning
confidence: 99%
“…However, the stoichiometry of this reaction differs substantially from that of the "classical" Schlesinger reaction, which diminishes the economical effect of the increase in С eff AlH 3 . In addition, the product formed is multiphase and decomposes rapidly to elements even at 60-70 °С.…”
mentioning
confidence: 87%
“…Presently, the most popular method for the syn thesis of this hydride is the thermal cleavage of etherate {AlH 3 •xEt 2 O}, which was obtained by the Schlesinger reaction 1 (Eq. (1)) in the presence of small amounts of lithium tetrahydridoaluminate and tetrahydridoborate (10)(11)(12)(13)(14)(15) wt.% of aluminum hydride) followed by crystal lization of nonsolvated aluminum hydride (hereinafter, NAH) from solutions in an ether-ArH mixed solvent.…”
mentioning
confidence: 99%
See 2 more Smart Citations